The efficacy of periprostatic local anaesthetic infiltration in transrectal ultrasound biopsy of prostate: a prospective randomised control study - Kuppusamy, S.; Faizal, N.; Quek, K.F.; Razack, A.H.; Dublin, N. (Springer Verlag (Germany), 2010)
It is still uncertain as to which form of anaesthesia is the optimum. We conducted a study to identify the best location and optimum volume of anaesthetic agent in order to achieve best pain relief and cooperation from our patients. We also assessed the need for local anaesthetic gel for probe lubrication and if the number of cores during biopsy makes a difference in the pain score. A total of 386 patients were randomised into 4 groups i.e. no anaesthesia (Group A), 10 cc 1% Lignocaine at apical region of prostate (Group B), 5 cc 1% Lignocaine each at both bases (Group C) and lastly, 4 cc at apex and 3 cc each at both bases (Group D). Pain assessment was performed using the 10-point Visual Analog Scale after the procedure with regard to probe insertion and during the biopsy. The groups were comparable in number and mean age. Group B recorded the lowest mean pain score of 2.59. Comparative analysis showed significant pain relief when comparing Group B vs. Group A (P = 0.001). The other groups were not as effective. The overall mean pain score for the probe insertion and the number of cores during biopsy was also not significant. We suggest that a 10 cc 1% Lignocaine infiltration at the apical region of the prostate be used to obtain best pain relief during this procedure. Plain lubricant jelly is sufficient for probe insertion. There is no need to alter the anaesthetic requirement if number of cores is increased.